Distribution of Inorganic Phosphorus Fraction in Rajasthan Soils - Ruhal, D S; Deo, Ram (Annals of Arid Zone, 2016)
Phosphorus distribution in some soil profiles of Rajasthan was examined. Tr.e amount of total, calcium, aluminium and iron phosphate declined with depth in all the soil profiles except the hilly soil, where total and calcium phosphate increased. Of the three fractions, calcium phosphate dominated in practically all cases ranging from 85.0 to 310 ppm and it was highest in surface layer of alluvial soils. Aluminium and iron phosphate varied from 3.5 to 38.0 and 6.5 to 24.0 ppm respectively. Total phosphorus correlated positively and significantly with the soil pH and organic carbon, whereas aluminium phosphate correlated negatively with pH of soi.ls. Calcium carbonate provided significant positive correlation with calcium phosphate and negative with aluminium and iron phosphate, whereas organic carbon correlated positively with calcium, aluminium and iron phosphate.